Long-term functional outcomes of patients with Hirschsprung disease following pull-through - Gunadi; Theodora Monica Carissa; Stevie; Ezzah Fatmala Daulay; Dicky Yulianda; Kristy Iskandar; Andi Dwihantoro (BMC, 2022)
Abstract Background Hirschsprung disease (HSCR) is a common congenital disorder presenting with functional obstruction due to aganglionosis of the colon. There are numerous types of pull-through surgery for managing HSCR, such as transabdominal endorectal (Soave), Swenson, Duhamel, transanal endorectal pull-through (TEPT), and laparoscopic (Georgeson) approach. Here, we aimed to describe the long-term outcome of patients with HSCR who underwent transabdominal Soave, Duhamel, and TEPT in our institution. Methods We performed a cross-sectional analysis for patients who underwent Duhamel, Soave, and TEPT at our institution from January 2012 to December 2015. Long-term functional outcome was determined by bowel function score (BFS). The BFS was obtained by interviewing patients who had completed at least three years of follow-up. Results Twenty-five patients were included in this study who underwent transabdominal Soave (n = 8), Duhamel (n = 4), and TEPT (n = 13). There were 24 patients with short aganglionosis type. The median age of HSCR diagnosis was 10 (IQR = 1-39) months, while the median age of pull-through surgery was 17 (IQR = 7-47) months. The median follow-up of BFS level for HSCR patients after pull-through was 72 (IQR, 54-99) months. There were 11 patients with good BFS level and 10 patients with normal BFS level. Additionally, 50% of Duhamel patients had poor BFS level, while 50% of Soave patients had good BFS level, and 54% of TEPT patients had normal BFS level (p = 0.027). As many as 50% of Duhamel patients showed daily soiling and required protective aids, while 38.5% of TEPT had staining less than 1/week and no change of underwear required, and 50% of Soave patients revealed no soiling, respectively (p = 0.030). Furthermore, 75% of Duhamel patients had accidents, while 75% of Soave and 46.2% of TEPT patients had no accidents (p = 0.035). Conclusion Our study shows that the type of definitive surgery might affect the long-term bowel functional outcome; particularly, the TEPT approach might have some advantages over the transabdominal Soave and Duhamel procedures.